Intermediate financial management. - Brigham, Eugene F.; Daves, Phillip R. (Mason, Ohio : South-Western ; Andover : Cengage Learning [distributor], 1985)
Give your students essential support as this invaluable tool lists key learning objectives for each chapter, outlines key sections, provides self-test questions, and a set of problems similar to those in the text and the Test Bank with fully worked-out solutions.
Previous ed.: 2010.
Includes bibliographical references and indexes.
Keywords: Business enterprises; Financial management